Influence of glucocorticoids and disease activity on total and high density lipoprotein cholesterol in patients with rheumatoid arthritis. Issue 9 (15th August 2003) - Boers, M; Nurmohamed, M T; Doelman, C J A; Lard, L R; Verhoeven, A C; Voskuyl, A E; Huizinga, T W J; van de Stadt, R J; Dijkmans, B A C; van der Linden, Sj
Abstract : Background: Glucocorticoids induce hypercholesterolaemia, a cardiovascular risk factor, in patients with diseases other than rheumatoid arthritis (RA), but the data in RA are contradictory. Objective: To determine the effects of antirheumatic treatment, including prednisolone (combination) therapy on total and high density lipoprotein (HDL) cholesterol levels in RA, taking disease activity into account. Methods: HDL cholesterol and total cholesterol levels were determined in:( a ) established RA ( b ) two cohorts with early active RA, ( c ) a previously conducted 56 week trial among patients with early RA comparing the value of intensive combination therapy (that included glucocorticoids) with sulfasalazine alone (COBRA trial). Results: In established RA total cholesterol levels were only slightly raised, irrespective of disease activity. However, HDL cholesterol was significantly higher in patients in remission than in patients with active disease. In contrast, in active early RA at baseline total cholesterol was low normal: between 4.6 and 5.1 mmol/l in the different populations. The level of HDL cholesterol was highly dependent on the duration of storage. In both COBRA groups total cholesterol increased by a mean of 0.6 mmol/l. HDL cholesterol increased by more than 50% after treatment, leading to an improvement of the total cholesterol/HDL ratio (atherogenic index). This increase (and index improvement) was much more rapid in the group receiving combination treatment. A similar pattern was seen in the 2001 cohort with early RA. In all the groups with active disease HDL and total cholesterol levels correlated inversely with disease activity. Conclusion: In established, but especially in early RA, disease activity is accompanied by atherogenic lipid levels. This dyslipidaemia can be rapidly reversed by aggressive antirheumatic treatment including glucocorticoids.